THE EFFECT OF SIZE AND FSR ON COMPANY VALUE (PBV) WITH THE MEDIATION OF LIQUIDITY IN THE HEALTHCARE SECTOR FROM 2022 TO 2024 - Disti Paremono Priatsaleh; Andini Nurwulandari; Irma Setyawati (International Journal of Social Science, 2025)
This study examines the effect of firm size and the Financial Sustainability Ratio (FSR) on firm value, measured by Price to Book Value (PBV), with liquidity as a mediating variable in the Indonesian healthcare sector during 2022–2024. The research is motivated by the rapid growth of the healthcare industry post-pandemic, accompanied by dynamic variations in firm value that are not always aligned with company size or financial sustainability. Using a purposive sampling method, 19 healthcare companies listed on the IDX were selected, with data drawn from annual reports and financial statements. The analysis employed panel data regression with the Random Effect Model (REM) and Sobel tests to assess mediation effects. The results indicate that both firm size and FSR negatively affect PBV, suggesting that larger firms and those with higher FSR may be perceived as less efficient or riskier by investors. Similarly, firm size and FSR also negatively impact liquidity (Current Ratio), showing that business expansion and debt-based structures may reduce short-term solvency. Regarding mediation, liquidity does not significantly mediate the relationship between firm size and PBV, indicating that market valuation of size occurs directly rather than through liquidity. However, liquidity is found to significantly mediate the effect of FSR on PBV, implying that firms with balanced financial structures and healthy liquidity levels are more positively valued by investors. Overall, the findings highlight that in the healthcare sector, investors place greater emphasis on efficiency, growth prospects, and prudent financial management rather than merely company scale or leverage.